“Urinator’s craftsmanship as rivers flow” or how water obstacles were breached in the 15th and 16th centuries - Strzyż, Piotr (Armia kontra natura, 2020)
In the past, people used various methods in order to cross water obstacles: they used fords, built bridges and rafts, or finally resorted to boats of different design. However, military treaties from those times also mention other solutions which could be used in special circumstances. They included special devices which allowed breathing and moving underwater, on the bottom of the reservoir. They were used by Urinatores, the people who could be entrusted with dangerous military sabotage actions against the enemy fleet as well as used for recovering military equipment lost in the water or clearing canals or rivers.Medieval and Renaissance iconography proves that the instruments occurred in two forms. The first was an inflatable leather belt, buckled on the stomach, with a flexible pipe attached to it. Additional equipment consisted of boots, suitably loaded with lead, and defensive and offensive weapon. The second variant of diving apparatus was a special leather bonnet, fitted with glass-protected eye openings and a long breathing hose with a float sewn to it. Prepared in this way, the diver could spend up to several hours under water. For the territory of the Kingdom of Poland, the relevant information can be found in Księgi Hetmańskie by Stanisław Sarnicki from the second half of the 16th century. Such specialists were certainly useful, but the job undertaken by them was extremely dangerous, particularly if we take into account how primitive the means at their disposal were.